2021
DOI: 10.1093/chromsci/bmab137
|View full text |Cite
|
Sign up to set email alerts
|

Forced Degradation Study of Zanubrutinib: An LC–PDA and LC–MS Approach

Abstract: Zanubrutinib is an unfamiliar second generation selective Brutson’s Tyrosine Kinase inhibitor used to treat mantle cell lymphoma. In the present analysis, a new, stability indicating reverse-phase, high performance liquid chromatography method was developed and validated for the determination of Zanubrutinib succeeding degradation studies as pert the International Conference on Harmonization guidelines. The chromatographic separation of Zanubrutinib was achieved in a C18 column (250 × 4.6 mm, 5-μm particle siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…[18][19][20] Therefore, it is essential to identify degradation pathways when developing formulation strategies and stability-indicating methods. 21,22 However, there is currently no systematic study reported on the degradation pathway of brivaracetam, 23,24 highlighting the need for further investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] Therefore, it is essential to identify degradation pathways when developing formulation strategies and stability-indicating methods. 21,22 However, there is currently no systematic study reported on the degradation pathway of brivaracetam, 23,24 highlighting the need for further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting degradation products (DPs) have the potential to affect the safety and efficacy of drugs, possibly leading to adverse effects and toxicity 18–20 . Therefore, it is essential to identify degradation pathways when developing formulation strategies and stability‐indicating methods 21,22 . However, there is currently no systematic study reported on the degradation pathway of brivaracetam, 23,24 highlighting the need for further investigation.…”
Section: Introductionmentioning
confidence: 99%